Loss of control during instrumental learning: a source localization study - Diener, Carsten; Kühner, Christine; Flor, Herta (NeuroImage, 2010)
This study used multi-channel electroencephalography (EEG) to investigate cortical correlates of response-outcome contingency appraisal as indexed by the postimperative negative variation (PINV) during instrumental learning. PINV data were subjected to standardized low resolution brain electromagnetic tomography (sLORETA) for source localization. Forty-six healthy adult persons underwent a forewarned S1-S2 paradigm where response-outcome contingencies varied in three consecutive conditions. Initially subjects could control aversive stimulation by a correct behavioral response followed by loss of control and subsequent restitution of control. Throughout the experiment, reaction times, errors, ratings of controllability, arousal, emotional valence and helplessness were assessed. Topographical EEG analyses showed that in particular frontal PINV magnitudes covaried with the experimental manipulation. Loss of control induced extensive response-outcome uncertainty accompanied by a fronto-central PINV maximum. sLORETA functional analyses of the PINV revealed that dependent on the experimental conditions frontal, temporal and parietal areas seem to be related to PINV formation. In particular during loss of control, between-conditions sLORETA comparisons found Brodmann Area 24 in the anterior cingulate cortex (ACC) to be associated with PINV generation, which was confirmed by correlational analyses. These results provide further evidence for the role of the ACC in detecting response conflict and its involvement in the generation of the PINV.
Gesehen am 08.05.2023